Replicated whole‐lake experiment reveals the ineffectiveness of stocking five example fish species in small lakes - Sven Matern; Johannes Radinger; Thomas Klefoth; Christian Wolter; Robert Arlinghaus (Fisheries Management and Ecology, 2025)
Fish stocking is common practice in fisheries management, but its effectiveness to support or increase stock size or catches is debated. In Lower Saxony, Germany, a controlled, replicated stocking experiment of five native fish species in eight gravel pit lakes Abramis brama ), showed high survival in at least one study year, indicating general survival of the stocking material. Fish marking with passive integrated transponders did not affect fish survival, except for roach ( Rutilus rutilus ), and can thus be ruled out as an explanation for the high post‐stocking mortality. We conclude that stocking failed to enhance stocks of five native fish species in small gravel pit lakes.